2020
DOI: 10.3389/fpsyg.2020.00694
|View full text |Cite
|
Sign up to set email alerts
|

Hot and Cool Executive Function in Elite- and Amateur- Adolescent Athletes From Open and Closed Skills Sports

Abstract: Background: Executive functions (EFs) not only play an important role in shaping adolescent's goal-directed, future-oriented cognitive skills under relatively abstract, non-affective conditions (Cool EF), but also under motivationally significant, affective conditions (Hot EF). Empirical evidence suggest a link between EF, exercise and physical activity, specifically elite adult athletes appear to outperform amateur athletes in Cool EF; however, no previous studies have examined the relationship between Hot an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 121 publications
3
19
2
1
Order By: Relevance
“…Meanwhile, there is a positive correlation between net/total score on IGT and score on the digital span backward but not the digital span forward in the present study, which may be most likely attributed to the asumption that digital span backward required more cognitive processing, especially depending on the executive resources [ 61 ]. These associations concurred with those shown in other previous studies [ 34 , 39 , 62 ]. However, different with previous researches during the DM processes, our present study showed an inconsistent performance that clinical symptoms were unrelated to DM processes.…”
Section: Discussionsupporting
confidence: 94%
“…Meanwhile, there is a positive correlation between net/total score on IGT and score on the digital span backward but not the digital span forward in the present study, which may be most likely attributed to the asumption that digital span backward required more cognitive processing, especially depending on the executive resources [ 61 ]. These associations concurred with those shown in other previous studies [ 34 , 39 , 62 ]. However, different with previous researches during the DM processes, our present study showed an inconsistent performance that clinical symptoms were unrelated to DM processes.…”
Section: Discussionsupporting
confidence: 94%
“…This is probably the reason why there is no difference between open and closed skill sport athletes in several other studies. These findings are thus consistent with other research [42] focused on the cognitive and executive functions of track-and-field athletes and handball players. The authors found no difference between athletes in terms of sport disciplines.…”
Section: Discussionsupporting
confidence: 92%
“…A questionnaire for sports biography was used to determine what type of sport the participants did and how often they exercised per week to participate in the intervention study. Since sport type determines differences in executive functions in elite athletes [ 33 , 34 ], the sports biography was categorized into static sports (self-paced activities in highly consistent circumstances, e.g., taekwondo, athletics, and dancing, etc. ), strategic sports (requiring the adaption to highly varying situations considering teammates, opponents, positions or objects, e.g., soccer, basketball, handball, and volleyball, etc.)…”
Section: Methodsmentioning
confidence: 99%